Respostas
respondido por:
0
∫5*sen(2x)*cos(2x) dx
Faça u = sen(2x) ⇔ du = 2 cos(2x) dx
Então fica: sen(2x)*cos(2x) = 1/2 u du
Daí ∫(1/2) u du = 1/2 ∫u du = 1/4 u² + C
Portanto:
∫5*sen(2x)*cos(2x) dx
= 5(1/4 u²) + C
= 5/4 sen²(u) + C
= 5/4 sen²(2x) + C
*-*-*-*-*-*-*-*-*-*-*-*
03/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
Faça u = sen(2x) ⇔ du = 2 cos(2x) dx
Então fica: sen(2x)*cos(2x) = 1/2 u du
Daí ∫(1/2) u du = 1/2 ∫u du = 1/4 u² + C
Portanto:
∫5*sen(2x)*cos(2x) dx
= 5(1/4 u²) + C
= 5/4 sen²(u) + C
= 5/4 sen²(2x) + C
*-*-*-*-*-*-*-*-*-*-*-*
03/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
Anônimo:
Tudo bem?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás